The Determinants of Strike Activity in Canada - Smith, Douglas (Relations industrielles / Industrial Relations, 1972)
Strikes are an integral part of the collective bargaining process and as such must be understood in relation to their determinants in order to properly evaluate the performance of that process. In spite of the importance of such knowledge there has been surprisingly little effort devoted to estimating empirical relationships.